Identification of the immunosuppressive effect of γδ T cells correlated to bone morphogenetic protein 2 in acute myeloid leukemia - Shuang Liang; Shuang Liang; Tianhui Dong; Keli Yue; Haitao Gao; Ning Wu; Ruoyang Liu; Yan Chang; Le Hao; Lijuan Hu; Ting Zhao; Qian Jiang; et al. (Frontiers in Immunology, 2022)
Description of immune landscapes in malignant microenvironment is critical to the improvement of therapeutic strategies for various tumors. Acute myeloid leukemia (AML) remains a severe life-threatening malignancy and often confronts treatment dilemma in clinic. Although γδ T cells exhibit independent and potent cytotoxicity against leukemic cells in vitro and in the mouse models, efficacy of γδ T cell-based immunotherapy on AML patients has seemed unsatisfying so far. How the anti-AML capacity of γδ T cells is suppressed in vivo remains elusive. Herein, we found an aberrant γδ T cells subset expressing CD25+CD127lowVδ2+ in the bone marrows of patients with newly diagnosed AML. The emergence of this subset was significantly associated with disease status and risk stratification as well as with the abnormally increased bone morphogenetic protein 2 (BMP2). Mechanistically, BMP2 could directly induce CD25+CD127lowVδ2+ γδ T cells (named as Reg-Vδ2) in vitro. The immunosuppressive features of Reg-Vδ2 cells were identified by combining immunophenotypical and functional data. Furthermore, inhibition of BMP2 pathway significantly blocked the emergence of Reg-Vδ2 cells and enhanced the anti-AML immunity in humanized mice. These findings not only provide a novel insight into the mechanisms of immunosuppression in the context of leukemia, but also suggest potential targets for the treatment of AML and other hematopoietic malignancies.